Fuzzy Technology Present Applications and Future Challenges - Collan, Mikael; Fedrizzi, Mario; Kacprzyk, Janusz; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book provides readers with a timely and comprehensive yet concise view on the field of fuzzy logic and its real-world applications. The chapters, written by authoritative scholars in the field, report on promising new models for data analysis, decision making, and systems modeling, with a special emphasis on their applications in management science. The book is a token of appreciation from the fuzzy research community to Professor Christer Carlsson for his long time research and organizational commitment, which have among other things resulted in the foundation and success of the Institute for Advanced Management Systems Research (IAMSR) at Åbo Akademi University, in Åbo (Turku), Finland. The book serves as timely guide for the fuzzy logic and operations research communities alike. .
Part I: Foundations -- Part II: Data Analysis, Decision Making and Systems Modeling -- Part III: Fuzzy Logic in Business and Industrial Practice.
Keywords: Computational intelligence; Operations research; Management science; Industrial engineering; Production engineering; Computational Intelligence; Operations Research, Management Science; Operations Research and Decision Theory; Industrial and Production Engineering